2022
DOI: 10.2166/wst.2022.088
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing textile wastewater produced by industries: characteristics, environmental impacts, and treatment strategies

Abstract: The textile industry is one of the most intensive industries in chemical products whose wastewater contains hazardous dyes, pigments, dissolved/suspended solids, and heavy metals. Hence, it is important to effectively treat the wastewater generated by this industry before releasing it into the environment. Though the field of textile wastewater treatment has made tremendous progress, the developed treatment methods should be improved further to make them economically viable and friendly. In this review, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 105 publications
1
29
0
Order By: Relevance
“…Noteworthy, the value of pH = 5.7 was selected as a reference level for a deeper investigation of the effect of other operating parameters, since it falls in the typical range of values for conventional textile industry wastewater (and obviously due to the observed excellent AO10 removal performances). 65 The above results could be interpreted in the light of recent investigations performed by Kim et al, 64 and concerning the identification of oxidants and formation mechanism for the H 2 O 2 /IO 4 − oxidation system. In fact, the authors found that IO 4 − is the dominant species under acidic conditions, and it undergoes a single electron reduction by H 2 O 2 to yield the highly reactive • OH species.…”
Section: Effect Of the Initial Solution Phsupporting
confidence: 54%
“…Noteworthy, the value of pH = 5.7 was selected as a reference level for a deeper investigation of the effect of other operating parameters, since it falls in the typical range of values for conventional textile industry wastewater (and obviously due to the observed excellent AO10 removal performances). 65 The above results could be interpreted in the light of recent investigations performed by Kim et al, 64 and concerning the identification of oxidants and formation mechanism for the H 2 O 2 /IO 4 − oxidation system. In fact, the authors found that IO 4 − is the dominant species under acidic conditions, and it undergoes a single electron reduction by H 2 O 2 to yield the highly reactive • OH species.…”
Section: Effect Of the Initial Solution Phsupporting
confidence: 54%
“…Large amount of water used in the pretreatment, dyeing, printing and finishing stages in the textile industries is polluted with dyes and released into the environment ( Hussain and Wahab, 2018 ; Yaseen and Scholz, 2019 ). Textile wastewater has very different characteristics in terms of environmental issues such as dark color, wide pH range, high temperature, high chemical and biological oxygen demand (COD and BOD), high concentration of dissolved solids, metal ions and high conductivity ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. 25 reviewed the textile wastewater treatment strategies with their environmental impacts and their characteristics. Similarly.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reviewed the electrochemical process, e.g., Rodrigues-Narvaez et al [24] reviewed the electrochemical oxidation process for textile wastewater treatment. Wang et al [25] reviewed the textile wastewater treatment strategies with their environmental impacts and their characteristics. Similarly.…”
Section: Introductionmentioning
confidence: 99%